Where pesticides go - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Ecological monitoring methods for the assessment of pesticide impact in the tropics Edited by I F Grant & C C D Tingle, NRI CTA DFID, 2002. 276 pp. ISBN 0 85954 543 1 CTA number 1100. 80 credit points